Experiencing world history and geography (Holt, Rinehart and Winston, a Harcourt Education Company, 2008)
Provides interactive activities designed to incorporate text sources, visual aids, and information from the textbook into learning experiences that involve a wide variety of skills and will reach students with different learning styles. Transparencies can be used with any appropriate text or activity designed by the teacher. Worksheets can be used with a variety of topics. A rubic for evaluation of students is included with each activity.